Sh2-205: II. Its quiescent stellar formation activity - Romero, Gisela Andrea (2009)
We present a study of active star-forming regions in the environs of the H II region Sh2-205. The analysis is based on data obtained from point source catalogues and images extracted from the Two-Micron All-Sky Survey (2MASS), Midcourse Space Experiment (MSX) and IRAS surveys. Complementary data are taken from a CO survey. The identification of primary candidates for star-formation activity is made following colour criteria and a correlation with molecular gas emission. A number of star-formation tracer candidates are projected on to two substructures of the H II region: SH 148.83–0.67 and SH 149.25–0.00. However, the lack of molecular gas related to these structures casts doubt on the nature of the sources. Additional infrared sources may be associated with the H I shell centred at (l, b) = (149°0′, −1°30′). The most striking active area was found in connection with the H II region LBN 148.11–0.45, where star-formation candidates are projected on to molecular gas. The analytical model of the ‘collect and collapse’ process shows that star-formation activity could have been triggered by the expansion of this H II region.